Even Unmanipulated Eyebrows Are Unreliable Landmarks for Evaluating Deviated Noses in Rhinoplasty - Su Jin Kim; Kun Hee Lee; Hong Ryul Jin (Clinical and Experimental Otorhinolaryngology, 2026)
Objectives. The eyebrow is a frequently used landmark in rhinoplasty. While caution is advisable when relying on manipulated eyebrows as a reference, there is a lack of evidence regarding the use of unmanipulated eyebrows as a landmark. This study aimed to assess the reliability of unmanipulated eyebrows as landmarks for evaluating deviated nose.Methods. We analyzed preoperative photographs of patients who underwent rhinoplasty. We established mid-canthal and mid-eyebrow lines by bisecting the intercanthal distance and the most medial points of the eyebrows, respectively. Measurements were taken from these midlines to assess the distance to each midpoint of the nose. Independent observers rated the photographs for perceived nasal deviation.Results. Measurable discrepancies between the mid-canthal and mid-eyebrow lines were observed in 76% of patients. All anthropometric measurements related to nasal deviation were significantly different between the two midlines (P